Sequential expression of miR-221-3p and miR-338-3p in Schwann cells as a therapeutic strategy to promote nerve regeneration and functional recovery - Li-Li Wen; Tian-Hao Yu; Yi-Zhan Ma; Xiao-Yan Mao; Tian-Rang Ao; Rabia Javed; Hirotomo Ten; Akira Matsuno; Qiang Ao (Neural Regeneration Research, 2023)
The functional properties of endogenous Schwann cells (SCs) during nerve repair are dynamic. Optimizing the functional properties of SCs at different stages of nerve repair may have therapeutic benefit in improving the repair of damaged nerves. Previous studies showed that miR-221-3p promotes the proliferation and migration of SCs, and miR-338-3p promotes the myelination of SCs. In this study, we established rat models of sciatic nerve injury by bridging the transected sciatic nerve with a silicone tube. We injected a miR-221 lentiviral vector system together with a doxycycline-inducible Tet-On miR-338 lentiviral vector system into the cavity of nerve conduits of nerve stumps to sequentially regulate the biological function of endogenous SCs at different stages of nerve regeneration. We found that the biological function of SCs was sequentially regulated, the diameter and density of myelinated axons were increased, the expression levels of NF200 and myelin basic protein were increased, and the function of injured peripheral nerve was improved using this system. miRNA Target Prediction Database prediction, Nanopore whole transcriptome sequencing, quantitative PCR, and dual luciferase reporter gene assay results predicted and verified Cdkn1b and Nrp1 as target genes of miR-221-3p and miR-338-3p, respectively, and their regulatory effects on SCs were confirmed in vitro. In conclusion, here we established a new method to enhance nerve regeneration through sequential regulation of biological functions of endogenous SCs, which establishes a new concept and model for the treatment of peripheral nerve injury. The findings from this study will provide direct guiding significance for clinical treatment of sciatic nerve injury.